Application Model of Nurse Electronic Rostering Software (NERS) In Hospital Ward - Rosly Zunaedi; Soenarnatalina M. Ahsan (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2021)
Introduction: Good scheduling arrangements are needed so that there is no physical, emotional and psychological fatigue to nurses, which will have a negative impact on the performance of nurses in providing services to patients. This study aims to develop an application model for the electronic rostering of nurses in the ward. Methods: The design in this study was Research and Development (R&D). The population of this study was all nurses who worked in the inpatient room. The sampling technique used was simple random sampling. Data for the assessment of scheduling characteristics were collected using questionnaire based on formulation of the problem and Focus Group Discussion (FGD). Data analysis is in descriptive form. Results: Most of the respondents considered that ward scheduling characteristics were sufficient (80.2%). The development of electronic rostering model emphasizes on optimizing the needs and distribution of nurses, equalizing shift and off, and reducing time for preparing schedules. The development of an electronic rostering model was also adjusted to the policies of the hospital regarding the nurses’ work scheduling method so that it can be implemented appropriately in the ward. Conclusion: The development of an electronic work scheduling model for nurses in the inpatient room includes: division based on the level of patient dependence, scheduling flexibility by proposing early holidays and leave, and reducing the duration of nurses' rostering preparation.